DIFFERENT EFFECTS OF PEAT DEGRADATION ON DISSOLVED ORGANIC CARBON AND NITROGEN - Kalbitz K.; Geyer S. (My University, 2002)
The dynamics of dissolved organic matter (DOM) are closely related to organic matter processes such as decomposition, humification, and stabilization of organic matter in soils. Nevertheless, it is unknown whether dissolved organic carbon (DOC) and nitrogen (DON) have an equal response to these processes. We analyzed DOC and DON concentrations of topsoil, groundwater, and surface water of six differently used sites characterized by differences in peat degradation. Carbon (13C, 14C) and nitrogen (15N) isotopes of DOM were related to a humification index in order to detect differences between DOC and DON at different stages of humification. The results show that intact peatlands had higher DOC concentrations than degraded peatlands. Clearly, DOC concentration depends on soil organic carbon content and therefore on the degree of peat degradation. However, intact and degraded peatlands showed similar DON and inorganic N concentrations suggesting that DON release is dependent on soil inorganic N rather than the organic N pool. Moreover, a high degree of peat degradation resulted in lower DOC/DON ratios than the C/N ratio of the solid phase indicating a preferential release of DON from soil organic matter. Further, δ13C ratios and the radiocarbon age of DOM increase with peat degradation and humification indicating a high C turnover, an increased microbial modification and age of DOC. On the other hand δ15N ratios decrease, probably as a result of N fertilization. The promoting effect of inorganic N on DON release and a high humification of DOM at sites treated with inorganic N fertilizers suggest that N fertilization promotes a release of amino acids depleted in 15N and subsequent condensation with carbohydrates to humic substances.